Tourism’s Impact on Economic and Human Development: Evidence from ASEAN 5 - Tan, Yan-Teng; Gan, Pei-Tha; Keh, Chia-Guan; Abd. Hadi , Fatimah Salwa; Mohammed Gamal , Awadh Ahmed (Economy of Regions, 2025)
Tourism can serve as a driver of economic development, but economic growth does not always lead to better human development outcomes. This is particularly evident in post-pandemic tourism when analyzed through the Human Development Index. Supporting Amartya Sen’s argument that well-being should not be measured by income alone, this paper evaluates the impact of tourism within the capability approach. The analysis extends beyond economic indicators to incorporate health, education, and living standards, offering a more comprehensive view of well-being. Focusing on ASEAN 5 countries, the study finds a significant long-term relationship between tourism and human development. Panel cointegration analysis shows that increased tourism activity enhances key human development indicators, particularly healthcare, education, and overall living standards. A well-developed tourism sector can thus contribute to broader societal well-being, aligning with Sen’s emphasis on expanding individual capabilities and improving quality of life. The study advocates for tourism strategies that prioritize human development alongside economic gains, fostering a healthier and more prosperous society. It also presents policy implications and recommendations for promoting tourism in ASEAN 5, addressing gaps in existing literature. Future research could explore whether similar relationships hold across different tourism sectors, such as eco-tourism, medical tourism, and sports tourism.